Creation Opportunities: Entrepreneurial Curiosity, Generative Cognition, and Knightian Uncertainty - Arikan, Asli M.; Arikan, Ilgaz; Koparan, Ipek (Academy of Management Review, 2020)
Creation theory suggests that opportunity formation is endogenous to the actions of entrepreneurs. However, this characterization of the opportunity formation process suggests at least two important questions that have yet to be fully addressed in the literature—one pertaining to early on in the opportunity formation process, and one to later in this process. The present paper proposes to address these two questions—in particular, through the integration of the theories of cognition with the creation theory of opportunities. The first question is as follows: "Given that individuals have no rational, profit-maximizing reason to begin the process of forming an opportunity under conditions of Knightian uncertainty, why do they do so?" The present paper suggests that entrepreneurial curiosity sparks the creation of opportunities. The second question is this: "In later stages of the opportunity formation, how do individuals create the many possible ways to exploit this opportunity?" Here, this papers posits that creating entrepreneurial opportunities under Knightian uncertainty includes the cognitive generative processes of entrepreneurs. These theoretical arguments, which extend the creation theory of opportunities, also have implications for the valuation and governance of creation opportunities.